Histopathological, biomechanical, and behavioral pain findings of Achilles tendinopathy using an animal model of overuse injury. Issue 1 (19th January 2015) - Jafari, Leila; Vachon, Pascal; Beaudry, Francis; Langelier, Eve
Abstract: Animal models of forced running are used to study overuse tendinopathy, a common health problem for which clear evidence for effective and accessible treatments is still lacking. In these models, pain evaluation is necessary to better understand the disease, help design and evaluate therapies, and ensure humane treatment of the animals. Therefore, the main objective of this study was to evaluate pain and pathologic findings in an animal model of moderate Achilles tendinopathy induced by treadmill running. Air puffs, instead of electrical shocks, were used to stimulate running so that pain associated with stimulation would be avoided. Pressure pain sensitivity was evaluated in vivo using a new instrumented plier, whereas spinal cord peptides were analyzed ex vivo with high‐performance liquid chromatography tandem mass spectrometry. Tendon histologic slides were semiquantitatively evaluated, using the Bonar score technique and biomechanical properties, using the traction test. After 8 weeks of treadmill running (2 weeks for adaptation and 6 weeks for the lesion protocol), the protocol was stopped because the air puffs became ineffective to stimulate running. We, nevertheless, observed some histologic changes characteristic of overuse tendinopathy as well as decreased mechanical properties, increased Substance P and dynorphin A peptides but without pressure pain sensitivity. These results suggest that air‐puffs stimulation is sufficient to induce an early stage tendinopathy to study new therapeutic drugs without inducing unnecessary pain. They also indicate that pain‐associated peptides could be related with movement evoked pain and with the sharp breakdown of the running performance. Abstract : e12265 The main objective of this study was to correlate pain and pathologic findings in an animal model of moderate Achilles tendinopathy induced by treadmill running. We observed some histologic changes characteristic of overuse tendinopathy as well as decreased mechanical properties, increased Substance P and dynorphin A peptides but without pressure pain sensitivity.